Micro-slippage effects in pre-rolling induced by a disturbed and undisturbed pendulum with spherical supports. (January 2014) - Gilavdary, Igor; Mekid, Samir; Riznookaya, Natalia
Dynamics of small free swings of a pendulum supported by two spherical balls pre-rolling on a flat basis are considered to investigate the occurrence of micro-slippage at the contact interface between the balls and the flat surface. The basic mechanisms of this micro-slippage are investigated, showing how geometric conditions could initiate and magnify micro-slippage rather than assuming that these effects are core characteristics in any rolling system. This article also discusses the energy dissipation of a ball slipping on a flat surface at pre-rolling caused by three mechanisms and the conditions enabling the decrease of energy dissipation of the pendulum and the influence of the basis vibrations.